Correlation between Students’ Reading Interest on Short Story and Students’ Translation Ability - Afifatu Khoirun Nisa'; Slamet Asari; Ulfatul Ma'rifah (Universitas Muhammadiyah Gresik, 2023)
This research aimed to determine the correlation between students’ reading interest on short story and students’ translation ability. This is quantitative research using the correlation method. Data were collected from online questionnaires and test. This research uses bivariate correlation analysis as a research design. Respondents in this research were 8th grade students of SMPIT Al-Ibrah of the 2020/2021 academic year in Gresik, East Java, Indonesia. This study found that students’ reading interest on short story had a positive and significant correlation to students’ translation ability with a rxy value of 0.969>0.349 (rtable value) at the level of significance 0.05.